Pengaruh Model Project Based Learning Terhadap Pemahaman Konsep dan Kemampuan Berfikir Kritis Peserta Didik Di Kegiatan Pelatihan Jurnalistik - Hisyam, Hisyam; Masitoh, Siti; Arianto, Fajar (LP. Ma'arif Janggan Magetan, 2024)
The purpose of this study is to determine the effect of the project-based learning model on concept understanding and there is an effect of the project-based learning model on the critical thinking ability of students in journalistic training activities. Quasi-experimental research design, with a nonequivalent pretest-posttest group design model, 70 research subjects divided into experimental and control groups. The results showed that both data were statistically normally distributed, the data were statistically homogeneous, and the results of the hypothesis testing of both data showed a significant effect. The conclusion informs that there is an effect of project-based learning model on concept understanding and there is an effect of project-based learning model on students' critical thinking ability in journalism training activities.